Artropoda predator penghuni ekosistem persawahan di daerah cianjur, jawa barat - Siti Herlinda; Aunu Rauf; Soemartono Sosromarsono; Utomo Kartosuwondo; Purnama Hidayat; Siswandi Siswandi (Jurnal Entomologi Indonesia, 2004)
Predatory arthropods inhabiting paddy rice ecosystems in Cianjur District, West Java. Predatory arthropods were surveyed in Cianjur District, West Java from July to November 1997, with objectives to observe the species of predatory arthropods inhabiting the ecosystems. Canopy-inhabiting and soil-dwelling arthropods were sampled using D-vac and pitfall traps, respectively. Results indicated that insecta and Arachnida were the most abundant predators in the ecosystem, with the total of 142 species. Predatory insects were dominated by Carabidae (27 species), and Staphylinidae (13 species) and spiders were dominated by Therididae (9 species), and Lycosidae (8 species). Thus, predatory-arthropods inhabiting the sawah ecosystems were very diverse.